Variability of In Vivo Recovery of Factor IX after Infusion of Monoclonal Antibody Purified Factor IX Concentrates in Patients with Hemophilia B - White, Gilbert C, II; Shapiro, Amy D; Kurczynski, Elizabeth M; Kim, Hugh C; Bergman, Garrett E; Mononine® Study Group (Thrombosis and Haemostasis, 1995)
Monoclonal antibody purified factor IX concentrate, Mononine® (Armour Pharmaceutical Company, Kankakee, Illinois, USA), is a recently developed replacement factor concentrate for the treatment of patients with hemophilia B. The pharmacokinetic properties of monoclonal antibody purified factor IX concentrate (MAb Factor IX concentrate) have been evaluated in only small samples of patients, and little is known about those factors that might influence in vivo recovery of factor IX after infusion in a larger patient population. In vivo recovery of factor IX was therefore evaluated for 80 different indications in 72 patients who received MAb Factor IX concentrate for the management of spontaneous or trauma-induced bleeding, or as prophylaxis with surgery. The average recovery after infusions for presurgical pharmacokinetic analysis (mean ± standard deviation) was 1.28 ± 0.56 U/dl rise per U/kg infused (range 0.41-2.80), and the average recovery after all infusions for treatment was 1.23 ± 0.49 U/dl rise per U/kg infused (range -0.35-2.92). Recovery values for multiple MAb Factor IX doses in a given patient were also variable; the average recovery was 1.22 ± 0.53 U/dl rise per U/kg given, and standard deviations ranged from 0.03 to 1.26. Patient age, weight, and MAb Factor IX concentrate dose minimally but significantly influenced factor IX recovery. There was no significant effect of either race, history of previous thrombotic complications during treatment with other replacement factor concentrates, or bleeding state on recovery. All of the patients treated with this preparation experienced excellent hemostasis, and no thrombotic complications were observed.